ATTEMPT TO IMPROVE PKN LEARNING OUTCOMES OF FIRST-GRADE STUDENTS THROUGH THE IMPLEMENTATION OF COOPERATIVE LEARNING MODELS TWO STAY TWO STRAY AT SDN 008 BANDUR PICAK IN KAMPAR - Nurhasniati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
his paper discusses the improvement of Civic Education learning outcomes of the first-grade students by applying Two Stay Two Stray as a cooperative learning model at SDN 008 Bandur Picak in Kampar, which was conducted for 1 month. The research subjects were 22 first-grade students. The type of research is classroom action research. Based on the results of the analysis and discussion, it can be concluded that the implementation of the Two Stay Two Stray cooperative learning model type can improve the first-grade students’ learning outcomes in the Civic Education learning subject at SDN 008 Bandur Picak in Kampar. It can be seen from changes in students’ learning outcomes in cycle 1 and cycle 2. In cycle 1, the average score of students’ learning outcomes was 70.9 incomplete category and increased in cycle 2 to 82.5 in the complete category. Based on the performance indicators, the research is considered to be successful if learning completeness reaches 75% of all students. It is because applying the Two Stay Two Stray provides opportunities for students to exchange experiences and knowledge. Hence, students understanding of the subject matter increases and can improve their learning outcomes in turn which the researchers so far have never applied the Two Stay Two Stray cooperative learning model.